Direct activation of the fibroblast growth factor-21 pathway in overweight and obese cats - Brinker, Emily J.; Towns, T. Jordan; Watanabe, Rie; Ma, Xiaolei; Bashir, Adil; Cole, Robert C.; Wang, Xu; Graff, Emily C. (Frontiers in Veterinary Science, 2023)
Feline obesity is common, afflicting ~25 - 40% of domestic cats. Obese cats are predisposed to many metabolic dyscrasias, such as insulin resistance, altered blood lipids, and feline hepatic lipidosis. Fibroblast Growth Factor-21 (FGF21) is an endocrine hormone that mediates the fat-liver axis, and in humans and animals, FGF21 can ameliorate insulin resistance, non-alcoholic fatty liver disease, and obesity. Activation of the FGF21 pathway may have therapeutic benefits for obese cats. In this preliminary cross-sectional study, ad libitum fed, purpose-bred, male-neutered, 6-year-old, obese and overweight cats were administered either 10 mg/kg/day of an FGF21 mimetic (FGF21; n=4) or saline (control; n=3) for 14 days. Body weight, food, and water intake were quantified daily during and two weeks following treatment. Changes in metabolic and liver parameters, intrahepatic triglyceride content, liver elasticity, and gut microbiota were evaluated. Treatment with FGF21 resulted in significant weight loss (~5.93%) compared to control and a trend towards decreased intrahepatic triglyceride content. Cats treated with FGF21 had decreased serum alkaline phosphatase. No significant changes were noted in liver elasticity, serum, liver, or metabolic parameters, or gut microbiome composition. In obese and overweight cats, activation of the FGF21 pathway can safely induce weight loss with trends to improve liver lipid content. This exploratory study is the first to evaluate the FGF21 pathway in cats. Manipulation of the FGF21 pathway has promising potential as a therapeutic for feline obesity. Further studies are needed to see if FGF21-pathway manipulation can be therapeutic for feline hepatic lipidosis.